Tantangan dan Peluang Implementasi Kurikulum Merdeka Jurusan Pendidikan Bahasa Arab Universitas Islam Negeri Mataram - Rizki, Dimas Prayana; Suparmanto, Suparmanto; Isdianti, Fatimatuz Zahrah; Santika, Santika; Adrianti, Nurlinda (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The independent curriculum is an improvement in the education system and is implemented through a driving school program to improve the quality of learning in schools. The research method used is qualitative research. Qualitative research is an approach to conducting research that is oriented towards natural phenomena or symptoms. The results of the research are that every opportunity that exists, there are challenges in it, including: a) Readiness of lecturers and staff, b) Complete infrastructure, c) Sufficient funds, d) Different assessments, e) Mastery of learning technology.